THE FIRST EXPERIENCE IN DIAGNOSING THE GEODYNAMIC MECHANISMS OF FOLDING BY THE FACTOR ANALYSIS OF FOLDED STRUCTURE PARAMETERS (GREATER CAUCASUS) - F. L. Yakovlev; E. S. Gorbatov (Геодинамика и тектонофизика)
This article is focused on identifying geodynamic mechanisms leading to formation of large crustal blocks in nature. A specific feature of our study is statistical analysis of the data obtained by the methods of tectonophysics and structural geology. The analyzed material included 24  detailed structural sections (almost500 kmin total length) of Greater Caucasus. The Meso-Cenozoic sedimentary cover, that was intensely folded in the Oligocene and Early Miocene, is 10–15 km thick. A structure balanced in strain amounts and sediments volumes was reconstructed for three stages in the development of the studied area: 1 – pre-folded, 2 – post-folded, 3 – modern post-orogenic. The ‘geometry of folded domains’ method was used. For this purpose, 505 structural domains were identified in the detailed structural sections, the pre-fold state for every domain were reconstructed, and all the domains were aggregated into 78 structural cells. The reconstructions were based on structural indicators measurable in the folds forming the folded domains. Each structural cell was characterized by six parameters: an amount of shortening; depths of the basement top in the pre-folded, post-folded, and modern stages (i.e. stages 1, 2, and 3, respectively); a calculated position of the eroded top of the sedimentary cover (i.e. amplitude of orogenic uplifting); and a difference between the basement depths in stages 1 and 3. For 78 structural cells, shortening is about 50 % on average (from 2–10 % to 67 %). An average modern depth of the basement top is13 km(from 2.2 to31.7 km). The amplitudes of uplifting and of the erosion of top of the sedimentary cover for large blocks are in a range from 9 to19 km. Steady combinations of these values forming certain structures have been detected on the studied areas. It was found that the depth of the basement top in stage 3 (modern) has tendency to keep the value similar to the depth acquired in stage 1 (pre-folded) generally. This effect may be caused by an isostasy.. A number of estimated high values of the pair correlations have a genetic meaning. Using the factor analysis (as generalization of pairs correlations), we detected two factors related to the geodynamic mechanisms leading to formation of the structures larger than the cells – of the crust, and the upper mantle. Factor F1 (shortening, 60 % weight) depends on the amount of shortening and is responsible for amplitudes of uplifting. Factor F2 (isostasy, 27 % weight) is related to the initial thickness of the cover; it is responsible for the stability of the depth of the basement top. Isostasy assumes significant changes in the density of rocks in the crust and mantle, including the obtaining of mantle density volumes by the large volumes of the crust rocks. The factor “isostasy” in such kind was not taken into account in geodynamic models earlier.